The Role Of Agricultural Groups In Increasing Rice Fields Production In The Village Of Bou, Lambandia Sub-Districict, Kolaka Timur District - Haerunianti Haerunianti; La Aman Tabia (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2021)
The purpose of this research is to: (1) Find out how much farmer's role is to increase rice production in Bou village. (2) Knowing the motivation level of farmers in following the farmer group activities. (3) Knowing the use of superior seeds and simultaneous planting can be influential in increasing the production of rice paddy fields. This research was conducted in Bou village. The sample determination used in this research is based on information obtained from farmers and farmer groups by using simple random Sampling (simple Random sample and cluster Sampling). The method of analysis used is a descriptive method, the scoring method, and the data analysis technique done on the Guttman scale to answer the obvious (assertive) and consistent.The results showed that the farmer Group had a big role to increase the production of rice paddy fields in the research area that we have implemented in Bou village Lambandia, East Kolaka District. Judging from the 5 indicators consisting of simultaneous planting, how to manage the water needs (irrigation), determination of planting times, pest and disease control, determination of the superior seeds to be used. The motivation level of farmers in following farmer group activities is the highest category. The role of the farmer group were proven through the media absorption information and means of planning the farmers through the counseling held by PPL especially in the planting simultaneously and the selection of superior seeds can increase production and produce crops as expected by the farmers. The farm business in Bou village can be maintained to remain a quality food land.